EFEKTIVITAS PENGGUNAAN MEDIA SCRAPBOOK PADA KETERAMPILAN MENULIS NARASI PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS IV A DI SD NEGERI JULANG KOTA BOGOR - Ririn Sofi Rahayu; Deddy Sofyan; Epon Nurlela (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study evaluates the effectiveness of scrapbook media in improving narrative writing skills of fourth-grade students at SD Negeri Julang, Bogor City, using a descriptive qualitative approach. The research methods include classroom observations, interviews, and document analysis of 27 students. The results show that the use of scrapbook media is effective in improving students' narrative writing skills. In observations, students actively engaged in creating scrapbooks to illustrate narrative stories, and interviews indicated they were more motivated and enthusiastic. Document analysis showed a significant improvement in the quality of students' writing after using scrapbook media. This suggests that using scrapbook media can be a good option in Indonesian language learning to enhance students' narrative writing skills.skills